Manipulation of financial statement reporting has an impact on financial information and affects company value - Marjohan, Masno (Diponegoro International Journal of Business, 2024)
This study aims to determine and analyze the effect of manipulation of financial statement reporting on firm value, as well as the consequences of financial statement information on companies listed on the Indonesia Stock Exchange. This research uses quantitative associative, the sampling technique used is purposive sampling. The sample size for this study was determined based on criteria obtained from 105 property and real estate industry companies listed on the Indonesia Stock Exchange within 5 years. The analysis techniques used include descriptive statistical analysis, panel data regression test, classical assumption test, and path analysis. The results showed that external pressures strongly influence financial statement reporting manipulation, emphasizing the need for organizations to overcome these pressures through alternative financing options. Industry characteristics also play an important role in the occurrence of manipulation, while rationalization and capability have minimal effects. In addition, external pressure, industry characteristics, rationalization, and capability jointly affect financial statement manipulation. Surprisingly, financial statement manipulation or fraud does not have a significant impact on firm value, as signaling theory explains its negative impact on investor confidence and stock prices. This study found that external pressure and industry dynamics play an important role in the incidence of report manipulation, while rationalization and capability.